Impact of Consultation on Hospital Outcomes and Resource Utilization for Patients with Acute Congestive Heart Failure. Issue 7 (July 2017) - Varga, Zoltan; Sabzwari, Syed Ali Rafay; Abusaada, Khalid
Abstract: Objectives: Consultation is an important tool for acquiring subspecialty support when managing patients with acute congestive heart failure (CHF). The effect of consultation on hospital outcomes and resource utilization in CHF is unknown. The objectives of our study were to determine the effect of consultation on outcomes in CHF and to evaluate factors affecting the frequency of consultation. Methods: Our study was a retrospective cohort study of patients admitted to Florida Hospital Orlando for CHF between January 1, 2011 and December 31, 2013. Data on demographics, number of consultations, length of stay (LOS), readmissions within 30 days, cost of care, and mortality were compared according to the number of consultations. For statistical analysis, analysis of variance, the χ 2 test, and multivariate linear regression analysis were used. Risk-adjusted outcomes were reported as observed/expected. Results: A total of 1554 patients were included; 103 (6.6%) patients received no consultation; 482 (31%) received 1; 365 (23.5%) received 2; 229 (14%) received 3; and 375 (24%) received ≥4. Teaching service, age, and African American race were associated with decreased consultation ( P < 0.001 for all) and high case-mix index was associated with increased consultation ( P < 0.001). Adjusted LOS and costs increased with an increased number of consultations ( P < 0.001 for both). There was no difference in adjusted mortality or 30-day readmission rate based on the number of consultations ( P = 0.35 and 0.98, respectively). Conclusions: Increased consultation with patients with CHF is associated with increased costs and LOS without improved mortality or readmission rate. Decreased utilization of consultations by the teaching service suggests that there is an opportunity to decrease utilization of healthcare resources by streamlining the utilization of consultations. Abstract : Consultation is an important tool for acquiring subspecialty support when managing patients in the hospital. Although many diagnostic and treatment strategies have been tested rigorously in the treatment of acute decompensation of congestive heart failure to determine whether they improve outcomes or decrease the utilization of healthcare resources, the effect of consultation has never been evaluated. The goals of this study were to determine the effect of consultation on outcomes in congestive heart failure and to evaluate factors affecting the frequency of consultation.